ANALISIS NILAI RELIGIUS DAN TINDAK TUTUR ILOKUSI DALAM TUTURAN IJAB KABUL DAN SIGHAT TAKLIK MASYARAKAT DESA LADAN, KABUPATEN KEPULAUAN ANAMBAS - Peharni, Rilda; Abdul Malik; Asri Lolita; Maulida Mustado; Robby Patria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the religious values and illocutionary speech acts found in the utterances of ijab kabul and sighat taklik in the marriage ceremony of the Ladan Village community, Anambas Islands Regency. This study employed a descriptive qualitative approach. The data consisted of utterances collected through observation, documentation, and transcription. The data were analyzed through transcription, identification, classification, interpretation, and conclusion drawing, while data validity was ensured through credibility, transferability, dependability, and confirmability. The findings reveal that the utterances contain religious values reflecting the relationship between humans and God, fellow humans, and themselves. In addition, various types of illocutionary speech acts were identified, representing declarative, directive, commissive, and expressive functions. These findings indicate that ijab kabul and sighat taklik utterances not only serve as essential components of the marriage ceremony but also embody religious values and communicative functions within the Islamic marriage tradition.